Diskresi Pejabat Imigrasi dalam Penerapan Tindakan Administrasi Keimigrasian (TAK) dan Implikasinya terhadap Pengenaan Sanksi Pidana - Atha Yanuar Rafi; Eric Theo Vanes Surbakti; Enggar Eka Fahrurriza (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study is motivated by the unclear boundaries of immigration officers’ discretion in the implementation of Administrative Immigration Actions (TAK), which has implications for the potential imposition of criminal sanctions. Discretion, as an instrument of administrative law, is fundamentally intended to address legal limitations in concrete situations. However, in practice, such discretion often leads to multiple interpretations and may be classified as an abuse of authority. The main issue lies in the blurred distinction between administrative authority and criminal violations, resulting in legal uncertainty and the risk of criminalizing immigration officers. This study aims to analyze the normative limits of discretion, examine its implications for criminal sanctions, and formulate efforts to strengthen legal certainty. The research employs a normative juridical method with statutory, conceptual, and case approaches. The data consist of primary, secondary, and tertiary legal materials analyzed using qualitative descriptive methods. The findings indicate that the ambiguity in the limits of discretion leads to an overlap between administrative and criminal law, thereby increasing the potential for criminalization. Therefore, it is necessary to clarify the boundaries of discretion, strengthen technical regulations, and harmonize legal frameworks to ensure legal certainty and protection.